Иннервация ротовой полости черноморских дельфинов - Гилевич, С.А.; Мангер, А.П. (Вестник зоологии, 1983)
It is stated that in dolphins the mouth floor muscles are innervated by mylohyoid and hypoglossal nerves. Buccal nerve innervates lip skin near mouth angles.The lower alveolar and lingual nerves participate in innervation of gingivae and mouth floor mucosas. A branching diagram of the mentioned nerve stems and their major branches in dolphins is similar to that in ferrestrial mammals. Certain distinctions are observed in the number and topography of small intraorgan branches. A sensitive nerve appratus of the mouth in dolphins is represented by free and not free nerve endings. Incapsulated nerve endings are the most distributed form of ceptors. A sharp polymorphism of the mouth ceptors in dolphins is due fo exogenic stimuli of various origin.